Pengaruh penambahan daun pohon terhadap kadar VFA dan kecernaan secara in-vitro ransum berbasis ketela pohon (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The purpose of this researchwasto findthe effect oftree leaves added into acassava biomass based ration on VFA concentration and in-vitro digestibility. This research used a randomized block design with 4 treatmentsand 3 groupsof replications. Feed treatment was composed by20% of cassava meal + 30% of cassava peel silage meal + 50% of leaf meal. P1was Manihot uttilissima leaf meal, P2was Gliricidia sepium leaf meal, P3was Moringa oleifera leaf meal and P4was Tectona grandis leaf meal. In-vitro incubation time was 48 hours in the syringe. The result showed that the value of gas production at hours12 hadsignificant differences(P<0.05) onthe treatments, with the highest values in P3. Gas production values ​​were significantlydifferent (P<0.01) at hours 24and 48. Theaveragedry matter digestibility (DMD)and in-vitro organic matter digestibility (OMD)was found the highest in P1 and P3. The highest VFA concentration was found in P3. The treatment had highlysignificanteffect (P<0.01) on the concentration of acetic acid (C2) andhad significant differences (P<0.05) on the concentrationofpropionic acid (C3),butyric acid (C4)and C2/C3 ratio. The concentration of CO2 and CH4 did not give significant differences (P>0.05). Theconclusion ofthis research was the addition of Manihot uttilissima leafmealand Moringa oleifera leaf meal was the best addition in cassava-based feedof that reviewedby in-vitro. Keywords: Cassava, in-vitro, gas production, leaf meal